1945
DOI: 10.1113/jphysiol.1945.sp004103
|View full text |Cite
|
Sign up to set email alerts
|

The regional distribution of sweating

Abstract: Kuno's monograph (1934) (Houghten, Teague & Miller, 1926) of 94°F. Every 20 min. during the first 2 hr. of each exposure the men performed a set amount of work. The work consisted of stepping on and off a stool, 1 ft. high, for 5 min., and the grade of work was altered by increasing the rate of stepping on and off. During the first exposure, the first three bouts of work were at such a rate that the men stepped on and off the stool twelve times per mi. and, for the last two, twenty-four times per min. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
1

Year Published

1952
1952
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 0 publications
6
72
1
Order By: Relevance
“…Areas of low sweat production were observed to be the sides of the chest, all extremities, and the internal femoral region. In contrast to the present data, Weiner (1945) found lower sweat rates on the posterior compared to anterior torso, however, the small sample size (n=3) may have been inadequate given the high variation in sweating between individuals. A medial to lateral decrease in sweat rate was observed across the torso in the present study and was similarly noted by Machado-Moreira et al (2008b) and Havenith et al (2008b), but not by Cotter et al (1995).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Areas of low sweat production were observed to be the sides of the chest, all extremities, and the internal femoral region. In contrast to the present data, Weiner (1945) found lower sweat rates on the posterior compared to anterior torso, however, the small sample size (n=3) may have been inadequate given the high variation in sweating between individuals. A medial to lateral decrease in sweat rate was observed across the torso in the present study and was similarly noted by Machado-Moreira et al (2008b) and Havenith et al (2008b), but not by Cotter et al (1995).…”
Section: Discussioncontrasting
confidence: 55%
“…Those that have investigated regional sweating observed considerable variation between the sites tested (Cotter et al 1995;Fogarty et al 2007;Havenith et al 2008a;Hertzman 1957;Kuno 1956;Machado-Moreira et al 2008a, b, c;Ogata 1935;Smith et al 2007;Taylor et al 2006;Weiner 1945). These studies consistently found sweat rates of the sampled sites to be greatest on the torso.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The absolute sweat rates 5 showed a large variation for the different zones within each sex group, and different zone 6 sweat rate ranges overlapped substantially. Nevertheless, significant differences in sweating 7 were observed. Overall, the effect of ZONE (within subjects) was highly significant 8 (p<0.0005), while the overall effect of SEX was not significant.…”
mentioning
confidence: 85%
“…Also the development of more sophisticated sweating thermal manikins, which 4 are now able to simulate sweat production in different body zones, require such data, as do 5 developers of mathematical models of human thermoregulation, where they want to include 6 regional differences. The present study was initiated with these applications in mind, and will 7 attempt to chart regional sweat rate on the upper body, covering the whole torso skin area and 8 the upper arms. In addition, attention will be given on how these sweat rates are different 9 between a group of males and females and how the sex of the participants affects the sweat 10 distribution.…”
mentioning
confidence: 99%